Caddyshack : the making of a Hollywood Cinderella story - Nashawaty, Chris (Flatiron Books, 2018)
"In the summer of 1980, a group of authority-defying comedy geniuses from Saturday Night Live, the Second City improv troupe, and the National Lampoon magazine created the funniest sports movie ever made. Maybe the funniest movie ever made, period. This timeless snobs-versus-slobs story of working-class kids and the white-collar buffoons who make them carry their golf bags in the hot summer sun has sex, drugs, and one very memorable candy bar. But the movie we all know and love as a benchmark of comedic film didn't start that way, and everyone who made it certainly didn't have the word "classic" in mind as the cameras were rolling. The story of Caddyshack began, improbably, at Harvard University, when three editors of The Harvard Lampoon (Doug Kenney, Rob Hoffman, and Henry Beard) decided to unleash their revolutionary humor on the world at large and publish the National Lampoon. The magazine quickly became a cultural juggernaut, expanding from page to stage and attracting the talents of John Belushi, Chevy Chase, Gilda Radner, and Bill Murray. Together, they set American popular culture on fire, and the Lampoon team quickly turned to film. After Animal House became a box office blockbuster, the brilliant and drug-addled minds of the Lampoon turned their focus on a story from Bill and Brian Doyle-Murray's childhood summers spent working at Chicago country clubs. The making of Caddyshack turned out to be even crazier and funnier than the film, as this ragtag group of party animal filmmakers descended on a Florida country club to shoot the movie over three very memorable months. In [this book], Chris Nashawaty, film critic for Entertainment Weekly, goes behind the scenes of the iconic film, chronicling the rise of comedy's greatest deranged minds as they turn the entertainment industry on its head and ultimately blow up both a golf course and popular culture as we know it. So, it's got that going for it ... which is nice."--Dust jacket.